Neutrophil-to-Lymphocyte and Platelet-to-Lymphocyte Ratios Are Correlated with Complicated Diverticulitis and Hinchey Classification: A Simple Tool to Assess Disease Severity in the Emergency Department - Amir Mari; Tawfik Khoury; Ahmad Lubany; Mohammad Safadi; Moaad Farraj; Amir Farah; Anas Kadah; Wisam Sbeit; Mahmud Mahamid (Emergency Medicine International)
Background and Aim. Rapid identification of patients with complications related to acute diverticulitis who require urgent intervention in the emergency department (ED) is essential. The aim of our study was to determine the role of neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) in predicting severity of diverticulitis as assessed by Hinchey classification. Patients and Methods. We performed a single retrospective study in EMMS Nazareth Hospital from 4/2014 to 4/2018. Patients were categorized into two groups: group A with mild to moderate complicated diverticulitis (Hinchey 1-2) and group B with severe complicated diverticulitis (Hinchey 3-4). Results. Two hundred twenty-five patients were included. Two hundred seven patients were in group A, and 18 patients were in group B. On univariate analysis, age, NLR, and PLR correlated with advanced Hinchey classification and disease severity (stages 3-4) (OR 1.038, 95% CI 1.001–1.076, P=0.0416; OR 1.192, 95% CI 1.093–1.300, P<0.0001; and OR 1.011, 95% CI 1.005–1.017, P=0.0005, respectively). On multivariate logistic regression analysis, the NLR and PLR remain significantly correlated with Hinchey 3-4 (OR 1.174, 95% CI 1.071–1.286, P=0.0006, and OR 1.008, 95% CI 1.001–1.015, P=0.0209, respectively). The area under the curve (AUC) for the NLR and PLR on univariate analysis was 0.7526 and 0.6748, respectively, and 0.7760 and 0.7391 on multivariate logistic regression analysis, respectively, and receiver-operating characteristic (ROC) curves were drawn. Conclusion. The NLR and PLR independently associated with diverticulitis severity and positively correlated with advanced Hinchey classification. This simple available laboratory tool can be implemented into clinical practice to optimize patient management.